Islamic Environmental Jurisprudence and Ecological Justice: A Case Study of the Tumpang Pitu Mining Conflict - Napitupulu, Abdul Khaliq; Syibly, M. Roem; Ilfansyah, Muhammad Ananda; Dinanta, Imam (Unisia, 2025)
The gold mining conflict in Tumpang Pitu, Banyuwangi, illustrates the clash between economic interests, environmental sustainability, and local community rights. This study aims to explore the relevance of environmental jurisprudence from an Islamic perspective, particularly in addressing ecological degradation and social inequality caused by mining activities. Using a qualitative case study approach, the research analyzes the environmental and social consequences of mining operations in Tumpang Pitu, focusing on Islamic principles such as environmental preservation, the objectives of Islamic law, and human responsibility as stewards of the earth. The findings reveal that the conversion of protected forests into production forests, driven by corporate and political interests, led to significant ecological damage, including floods and deteriorating water quality. Local communities, particularly fishermen, have suffered from the environmental degradation that mining caused. The study highlights how Islamic environmental jurisprudence provides a framework for ecological justice, advocating for sustainable practices and equitable resource distribution. It underscores the importance of integrating Islamic values into environmental policy and development, emphasizing the need for a holistic approach that combines spirituality, rationality, and social responsibility. Ultimately, this research calls for the adoption of environmental jurisprudence as a foundation for promoting ecological sustainability and justice in the face of modern industrial practices.